Wildlife survey along the Rawog River Conservation Area, Segaliud Lokan Forest Reserve - Jepthe Sompud; A. Ambrose; E. A. Gilbert; A. J. Embug; Suzeanywati Gasinin; N. Muroi; K. Kos (Sabah Forestry Department, 2019)
The Rawog river that stretched along the Rawog Conservation Area is one of the two rivers within the Segaliud Lokan Forest Reserve. Nonetheless, there is still scarce studies that document the wildlife that inhabit along this river. As such, limited information is available to describe the qualities of the Rawog river as part of the protected area. Therefore, this study was conducted during the Rawog Scientific Expedition with the aim to document and update the wildlife that includes birds, terrestrial mammals and crocodile that can be found along that river. Opportunistic observation survey was conducted for both morning and night sessions during the 4 days of expedition. A total of 61 individuals from 31 species and 24 families of wildlife were recorded. Interestingly, there were Endangered species of bird namely the Storm's Stork (Ciconia stormi) and one species with Vulnerable status that is Greater Green Leafbird (Chloropsis sonnerati) sighted during the survey. Meanwhile, for terrestrial mammals, there one Endangered species namely the Flat-headed cat (Prionailurus planiceps) and one Near-Threatened species of amphibian of which, is the Greater Swamp Frog (Limnonectes ingeri) were also able to be recorded even though there were no crocodile spotted during the survey. The result from this preliminary survey showed that the Rawog river play an important role in supporting diverse species of wildlife and worth to be retained as the fully protected area inside the Segaliud Lokan Forest Reserve.